Surface energy evaluation using a modified 3-D M-integral for multiple surface cracks. (1st December 2020) - Chang, J.H.; Yang, J.S.
Abstract: In the present paper, we develope a 3-D Msrf -integral to evaluate the surface energy that is corresponding to formation of multiple surface cracks. The Msrf -integral is formulated by modifying the conventional 3-D M-integral with deliberate origination of the coordinate system and proper delimitation of the integral surface. The integral is demonstrated to be surface-independent in a modified manner and so can be accurately evaluated provided an integration surface remote from the crack fronts is selected. With this feature, the theory of integration can be straightforwardly incorporated into the finite element method. In fact, it is not necessary to simulate the near-front regions with very fine FE simulations to obtain accurate solutions of Msrf .